The role of cell wall organization and active efflux pump systems in multidrug resistance of bacteria - (:unkn) unknown (ANKARA MICROBIOLOGY SOC, 2007)
Multiple antibiotic resistance of clinically important bacteria are of major concern worldwide. Alterations of drug targets or enzymatic inactivation of antimicrobial agents are the well known mechanisms of antimicrobial drug resistance. Besides these well known mechanisms, recent studies have shown that a further resistance mechanism, active drug efflux, has become increasingly important in the current threat of multidrug resistance. It involves certain bacterial transport proteins which pump out toxic antimicrobial compounds from the cell. Drug eff lux pump proteins in bacteria fall into five distinct protein super families [ATP binding cassette super family (ABC), Major facilitator super family (MFS), Small multidrug resistance super family (SMR), Multidrug and toxic compound extrusion (MATE) super family, Resistance-nodulation-cell division (RND) super family] and are mostly encoded by chromosomal genes. Among them, the members of RND protein super family are widely distrubuted in Gram negative bacteria and play siginificant role in both, intrinsic and acquired multidrug resistance of these bacteria with very wide substrate specificity. RND type multidrug efflux proteins usually function together with an outer membrane canal protein (OMP) and a membrane fusion protein (MFP) to pump out drugs. AcrAB-TolC of Escherichia coli and MexAB-OprM of Pseudomonas aeruginosa are the typical examples of these tripartite systems. They are constitutively expressed in wild type cells and play significant role in intrinsic resistance of these bacteria. However, multidrug resistance which is of major clinical significance, rises as a result of overexpression of these pump systems due to mutations and elevated levels of resistance are recorded to structurally unrelated antimicrobial drugs such as fluoroquinolones, beta-lactams, tetracyclines, chloramphenicol, trimethoprim, aminoglycosides and toxic compunds. Synthesis of RND type pump proteins are regulated by complex genetic mechanisms and global activator proteins (MarA, SoxS, Rob) are significant in the induction of overexpression of these efflux pump systems. Outer membrane of Gram negative bacteria with its unique lipopolysaccharide rich structure also contributes to drug eff lux and other antimicrobial resistance mechanisms by reducing the influx rate of toxic antimicrobial compunds. Multidrug efflux pump proteins found in Gram positive bacteria and mycobacteria are usually the members of protein super families other than RND family and their substrate profiles are more limited. However, some of these efflux proteins (NorA, MsrA, QacA in Staphylococcus aureus; PmrA and EmeA in Streptococcus pneumoniae) have clinical significance in the resistance to several antimicrobial agents (fluoroquinolones, macrolids) and toxic substances (quarternery ammonium compounds). In this review article, the role of cell wall organization and active efflux pump systems in multidrug resistance of bacteria have been discussed.
Keywords: active drug efflux; multidrug resistance; outer membrane; GRAM-NEGATIVE BACTERIA; PSEUDOMONAS-AERUGINOSA; ESCHERICHIA-COLI; OUTER-MEMBRANE; FLUOROQUINOLONE RESISTANCE; MYCOBACTERIUM-TUBERCULOSIS; ENTEROBACTER-AEROGENES; STAPHYLOCOCCUS-AUREUS; MEDIATED RESISTANCE; PORIN CHANNELS